2014
DOI: 10.2135/cropsci2013.08.0546
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Biomass and Nitrogen Accumulation Rates and Radiation Use Efficiency in a Maximum Yield Environment

Abstract: Soybean [Glycine max (L.) Merr.] physiological characterization in a maximum yield environment may identify yield‐optimization factors, lead to reassessment of fundamental crop model parameters, and provide guidance for management or breeding efforts. From 2011 to 2013, we characterized biomass and N accumulation rates, radiation use efficiency (RUE), and yield for four or five cultivars in a maximum‐yield contest field. Grain yield among cultivars ranged from 5290 to 7953 kg ha−1. The highest yields were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 35 publications
1
36
3
Order By: Relevance
“…The maximum RUE obtained in the current study (1.68 g MJ −1 for Hatsusayaka in 2015) was 17 to 32% higher than previously reported high RUE values in Japan: 1.40 g MJ −1 (Shiraiwa et al, 1994), 1.26 g MJ −1 (Nakaseko & Goto, 1983), and 1.15 g MJ −1 (Sinclair & Shiraiwa, 1993 ) were determined for high-yielding soybean in Missouri, U.S.A. (Van Roekel & Purcell, 2014). The high RUE in the current study could have resulted from the vigorous growth Table 4.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The maximum RUE obtained in the current study (1.68 g MJ −1 for Hatsusayaka in 2015) was 17 to 32% higher than previously reported high RUE values in Japan: 1.40 g MJ −1 (Shiraiwa et al, 1994), 1.26 g MJ −1 (Nakaseko & Goto, 1983), and 1.15 g MJ −1 (Sinclair & Shiraiwa, 1993 ) were determined for high-yielding soybean in Missouri, U.S.A. (Van Roekel & Purcell, 2014). The high RUE in the current study could have resulted from the vigorous growth Table 4.…”
Section: Discussioncontrasting
confidence: 60%
“…In their review of RUE, Sinclair and Muchow (1999) ) was reported for high-yielding soybean in Missouri, U.S.A. (Van Roekel & Purcell, 2014). In Japan, the previously reported high The field was fertilized with compound fertilizer before sowing at rates of 20, 56, and 56 kg ha −1 of N, P 2 O 5, and K 2 O, respectively.…”
Section: Experimental Site Cultivars and Field Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of N in soybean shoots in R3 was positively correlated with grain yield (r=0.75). High-grain yields of soybeangreater than 5 Mg ha -1 -is subjected to high rates of accumulation of dry matter and N by the crop (Van Roekel & Purcell, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Average irrigated and rainfed on-farm soybean yields in Nebraska (3.9 and 2.9 Mg ha −1 , respectively) are well below maximum yields of 6 to 7 Mg ha −1 measured in optimally-managed, non-water limited experimental trials and in credibly documented yield contest-winning fields across the U.S. Corn Belt. This has led to several reports commenting on the degree of the difference between producer yield and Y P , hereafter referred as the yield gap (Y G ) (Specht et al, 1999;Sinclair and Rufty, 2012;Van Roekel and Purcell, 2014). However, published data on the magnitude of soybean Y G are scarce.…”
Section: Introductionmentioning
confidence: 99%